Simulation and Measurement of Dielectric Antennas at 150 GHz - Weinzierl, Jochen; Richter, Jürgen; Rehm, Guenther; Brand, Hans (Proceedings of the 29th European Microwave Week, 1999)
Based on the development of a flexible, dielectric waveguide system for frequencies in the region of 150 GHz [1], the antenna characteristics of various tapered ends of dielectric waveguides have been studied. The flexible waveguide consists of a rectangular, dielectric fibre made of polyethylene. The paper describes the simulation and optimization of different tapers using 3D electromagnetic field computation, the precise fabrication of the antennas and the verification of the simulated data by field measurements at 150 GHz. © 1999 IEEE.
UnivIS-Import:2015-04-16:Pub.1999.tech.IE.LEH.simula